Model-based analysis of myocardial strains in left bundle branch block - Taconné, Marion; Owashi, Kimi P.; Galli, Elena; Duchenne, Jürgen; Hubert, Arnaud; Donal, Erwan; Hernàndez, Alfredo I.; Le Rolle, Virginie (Frontiers in Applied Mathematics and Statistics, 2022)
Introduction Although observational studies of patients with left bundle branch block (LBBB) have shown a relation between strain morphologies and responses to cardiac resynchronization therapy (CRT), the evaluation of left ventricle (LV) dyssynchrony from echocardiography remains difficult. The objective of this article is to propose a patient-specific model-based approach to improve the analysis and interpretation of myocardial strain signals. Methods A system-level model of the cardiovascular system is proposed, integrating: (i) the cardiac electrical system, (ii) right and left atria, (iii) a multi-segment representation of the RVs and LVs, and (iv) the systemic and pulmonary circulations. After a sensitivity analysis step, model parameters were identified specifically for each patient. The proposed approach was evaluated on data obtained from 10 healthy subjects and 20 patients with LBBB with underlying ischemic (n = 10) and non-ischemic (n = 10) cardiomyopathies. Results A close match was observed between estimated and observed strain signals, with mean RMSE respectively equal to 5.04 ± 1.02% and 3.90 ± 1.40% in healthy and LBBB cases. The analysis of patient-specific identified parameters, based on bull's-eye representation, shows that strain morphologies are related to both electrical conduction delay, and heterogeneity of contractile levels within the myocardium. Discussion The model-based approach improve the interpretability echocardiography data by bringing additional information on the regional electrical and mechanical function of the LV. The analysis of model parameters show that septal motion and global strain morphologies are not only explained by electrical conduction delay but also by the heterogeneity of contractile levels within the myocardium. The proposed approach represents a step forward in the development of personalized LV models for the evaluation of LV dyssynchrony in the field of CRT.